Students’ Perception About Reading Difficulties At The Eleventh Grade Students Of SMK Perbankan Yaris - Ghozi Roid Athallah (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
The purpose of this research was to find out students' perception of reading difficulties at SMK Perbankan Yaris Duri. This study investigated the eleventh grade students' perceptions of reading difficulties at SMK Perbankan Yaris, aimed to identify key challenges, and explored their underlying causes. Data were collected through a questionnaire distributed to 12 students and analyzing using descriptive statistics. The findings this study revealed that students faced several challenges in reading English texts, particularly in understanding long sentences, recalling information, and maintaining concentration. Students struggled with recalling information they had just read, particularly when dealing with lengthy or information-dense passages. Some students reported that they became confused or discouraged when encountering difficult words or unfamiliar topics, leading them to abandon reading tasks or skim without understanding. These findings suggest that enhancing students’ concentration skills, through strategies such as guided reading and chunking information, could improve their reading performance.